Old polish Christmas carols by contemplative nuns (seventeenth and eighteenth centuries) - Gwioździk, Jolanta (Interdisciplinary Studies in Musicology, 2018)
Old Polish Christmas carols in the contemplative female orders of Benedictine nuns, Poor Clares and Carmelite nuns were written and functioned at the junction of traditions - Polish and European, lay and religious, noble and elite, monastic and folk - and also in the Polish borderlands, which exhibited great diversification in terms of nationalities, religious denominations and cultures. The numerous versions of carols confirm not only their popularity, but also the fact that they functioned in specific environments, with the mutual influence of various motives, particularly noticeable in this genre, which was susceptible to all sorts of interference. The singing of carols, including those types which were characteristic of the monastic environment, such as lullabies, religious carols, songs of the nativity and of adoration and New Year carols, was a traditional part of Christmas celebrations. Performed both as part of the liturgy and outside it, they constituted a sort of a paratheatrical spectacle, characteristic of the Baroque mentality and of the spirituality of a specific order.